The real-world effectiveness of preschoolers wearing masks on campus to prevent respiratory infectious diseases: a cohort study - Yang, Wenhao; Liu, Jian; Qin, Nanyang (Frontiers in Public Health, 2024)
Background: Respiratory infections are common in the pediatric population.Preschoolers, especially those in kindergarten and 3 to 6 years old, are highly vulnerable to various respiratory infections.Objective: To investigate the efficacy of indoor mask-wearing in mitigating respiratory infections in preschoolers in a real-world campus setting.The study was conducted over a 115-day period in a kindergarten. Eligible children were assigned into study and control groups. The study group wore masks indoors but not outdoors, and the control group did not wear masks in either setting.We used a questionnaire to collect participant information, including age, height, weight, monthly dietary living expenses, family annual income, parent education level, primary caregiver, number of family members, and number of children under 6 years of age in the household. Incidences of clinical respiratory infections were recorded.We calculated the relative risk and analyzed the relationship between mask-wearing and respiratory infections by inter-group comparison, logistic regression, and Cox regression analyses.Results: A total of 135 preschoolers were included, with 35 and 100 preschoolers in the study and control groups, respectively. Baseline comparisons showed a significant difference in the number of children under 6 years old in the household between the two groups. Mask-wearing did not significantly reduce the risk of respiratory infections (RR = 1.086, 95% CI: 0.713, 1.435). Logistic and Cox regression analyses also showed no significant relationship between mask-wearing and occurrence of respiratory infections after controlling for potential confounders (OR = 0.816, 95% CI: 0.364, 1.826, and HR = 0.845, 95% CI: 0.495, 1.444).Conclusions: Indoor mask-wearing did not reduce the incidence of respiratory infections in preschoolers in a real-world campus setting. However, this study included a small number of preschoolers and observed them for a short period of time.Preschoolers were instructed to wear masks only when indoors. These factors could lead to bias and limit the generalizability of the study results.